RATES OF SILICATE DISSOLUTION IN DEEP-SEA SEDIMENT: IN SITU MEASUREMENT USING 234U/238U OF PORE FLUIDS - Maher K.; DePaolo D.J.; Lin J.C.F. (My University, 2004)
Bulk dissolution rates for sediment from ODP Site 984A in the North Atlantic are determined using the 234U/238U activity ratios of pore water, bulk sediment, and leachates. Site 984A is one of only several sites where closely spaced pore water samples were obtained from the upper 60 meters of the core; the sedimentation rate is high (11–15 cm/ka), hence the sediments in the upper 60 meters are less than 500 ka old. The sediment is clayey silt and composed mostly of detritus derived from Iceland with a significant component of biogenic carbonate (up to 30%).